Evaluasi Website PT Inti Diva Mandiri Menggunakan Metode Design Thinking - Setiabudi, Richard Indra; Ziveria, Mira (UNIVERSITAS KALBIS, 2025)
A website requires an attractive design so that users can be comfortable and interested in processing the information contained on the website. User interface and user experience are two important things that cannot be separated in the design process of a digital product. This study discusses the problems faced by website users of PT. Inti Diva Mandiri. This study aims to solve the problem with a solution in the form of an interface design. This research uses qualitative research methods. Researchers used the design thinking method as a data processing method. In the data processing stage, the researcher used figma and user experience questionnaire (UEQ) as testing instruments. The results of the study are prototypes and UEQ predicate values.